ALUN-ALUN EMPANG BOGOR: DINAMIKA TATA RUANG PEMERINTAHAN TRADISIONAL BOGOR PADA MASA KOLONIAL - Flourentina Dwiindah Pusparini (RUSTIC, 2022)
Bogor, during the colonial period, had a traditional government center in the form of an alun-alun, known as Alun-Alun Empang. This study aims to explore the dynamics of the development of the alun-alun, including what factors are behind its appearance, how the process was formed, and what its functions were in the colonial era. The study used the historical method. The primary sources used were maps of De Haan (1798, 1821, and 1830), the city maps of Buitenzorg (1901, 1921, 1930, and 1946), and literature related to alun-alun. The results showed that in the pre-colonial period (VOC), the traditional government center of Kampung Baru in Sukahati still applied Javanese cosmology; this can be seen in the orientation of the regent's house and the pool (empang in Sundanese) that stretches north-south with an imaginary axis towards the sea at the top and towards Mount Salak in the south. After the planning of the capital city of Buitenzorg in the 19th century, the Dutch East Indies colonial government built a square-shaped alun-alun with macapat concept in front of the regent's house. In addition to its role as a symbol of colonial power and a place for people to gather, alun-alun also developed into a center of economic, cultural and religious activity due to the impact of Wijkenstelsel in 1835-1915.